The mythology of sacred marriage in several works of european literature and in H. Tumanian's "Akhtamar" (an attempt of comparative analysis) - Margaryan, Siranush
IIn the article, we have considered several literary embodiments of the mythologeme ofsacred marriage, when it, retaining the memory of the pretext and symbolic system, undergoes various transformations in different periods and by different authors, absorbs peculiar and significant historical-philosophical, psychological, aesthetic and ethno-cultural nuances. The legend of a young man in love swimming from shore to shore, derived from the mythologeme of the sacred marriage, the origins of which go back to the Ancient Greece, is a universal plot in the ancient mythology (the legend of Hero and Leander) with deep problems, the changes of which depend on the interaction of reality and poetry, man, nature and society, as well as on the typology of the work, the aesthetic concept and worldview of the author. Հոդվածում քննության ենք առել սրբազան ամուսնության միֆոլոգեմի մի քանի գրական իրացումներ, երբ այն, պահպանելով իր նախատեքստի ու նշանային համակարգի հիշողությունը, տարբեր ժամանակաշրջաններում և տարբեր հեղինակների մոտ հանդես է գալիս ամենատարբեր փոխաձևություններով՝ ներառելով պատմափիլիսոփայական, հոգեբանական, գեղագիտական ու էթնո-մշակութաբանական յուրահատուկ ու իմաստակիր երանգներ։ Սրբազան ամուսնության միֆոլոգեմից ածանցված ափից ափ լողացող սիրահար պատանու ավանդությունը, որի ակունքները Հին Հունաստանում են, հնագույն դիցաբանության մեջ (Հերոյի և Լեանդրի ավանդազրույցը), համապարփակ ու խոր հարցադրումների սյուժե է, որի փոփոխությունները կախված են իրականության ու պոեզիայի, մարդու, բնության, հասարակության փոխհարաբերություններից, ստեղծագոր-ծության տիպաբանությունից ու հեղինակի աշխարհայացքից, գեղագիտական կոնցեպցիայից։ В статье нами рассмотрено несколько литературных воплощений мифологемы священного брака, когда она, сохраняя память о предтексте и символической системе, подвергается в разные периоды и у разных авторов разнообразным трансформациям, вбирая своеобразные и значимые историко-философские, психологические, эстетические и этнокультурные оттенки.Легенда о влюбленном юноше, плывущем от берега к берегу, производная от мифологемы священного брака, истоки которой уходят в Древнюю Грецию, в античноймифологии (легенда о Геро и Леандре) представляет собой универсальный сюжет спостановкой глубоких проблем, изменения которого зависят от взаимодействия реальности и поэзии, человека, природы и общества, типологии произведения, эстетической концепции и мировоззрения автора.
Keywords: Literary Studies